Construction of the matrix of individual nursing competences in surgical units - Laura Andrian Leal; Silvia Helena Henriques; Fabiana Faleiros Santana Castro; Mirelle Inácio Soares; Cléria Bragança; Beatriz Regina da Silva (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: to build and to describe an Individual Skills Matrix for nurses working in surgical units and their associated behaviors / attitudes. Method: Exploratory, qualitative study. 43 nurses from five surgical units participated, and data collection was carried out between April and September 2017. The focus group technique was used and for data interpretation an inductive thematic analysis was performed. The competence matrix was built from the testimonies of the participants plus a search in the literature for concepts directed to each competence and description of the expected behaviors and / or attitudes. Results: For the Matrix, the following individual skills were identified: Planning; Communication, Relational Competence, Leadership, Decision Making and Ethics. Final Considerations: The construction of a Matrix should assist managers in recognizing the professional profile and assessing their performance, strengthening the achievement of professional and organizational objectives, as well as contributing to the quality and effectiveness of the care provided by nurses in these places.